Investigation of effective parameters in the production of alumina gel through the sol-gel method - Rusul Alabada; Mustafa M. Kadhim; Zainab sabri Abbas; Ahmed Mahdi Rheima; Usama S. Altimari; Ashour H. Dawood; Alaa dhari jawad al-bayati; Zainab Talib Abed; Rusul Saeed Radhi; Asala Salam Jaber; Safa K. Hachim; Farah K. Ali; et al. (Case Studies in Chemical and Environmental Engineering, 2023)
Sol-gel chemistry is currently applied as one of the most widely used methods for synthesis of nanoparticles. In this method hydrolysis and poly-condensation reactions occur when the gel precursors are mixed with water and catalyst. The further condensation of sol particles into a three-dimensional network produces a gel. There are several parameters that effect on gelation time such as the molar ratio of alkoxide to water, the rate of hydrolysis, the type and amount of catalyst used, initial concentration of precursors and the temperature of hydrolysis and drying. Encapsulated solvent can be removed from a gel by either evaporative drying or supercritical drying. Where the resulting solids are known as a xerogel and an aerogel, respectively. During the drying process due to the surface tension of the liquid, a capillary pressure gradient is built in the pore walls, which is able to collapse most part of the pore volume. The volume shrinkage may be prevented by supercritical drying. The strength, thermal stability, pore structure and morphology of aerogels are keys to success for wider applications such as catalyst supports, thermal and acoustic insulators and adsorbents. Among catalyst support materials, alumina became popular recently due to its highly thermal and chemical stability and higher porosity. In the present study, synthesis of alumina gel as a support for nano-catalysts through hydrolysis of aluminum tri-sec-butoxide (ASB) in ethanol was investigated. The gel synthesis was carried out at 32 and 60 °C with different concentrations of water and precursor and different types and amounts of acid as catalyst. Rate of gel formation, efficiency of hydrolysis and polymerization and amount of gel production were measured and discussed. Results showed that acid addition around 0.2 ml and water to ASB malar ratio of 2 at 60 °C maximized the amount of gel produced and minimized the gelation time. Then, the alumina gel that synthesized at optimum conditions was dried by two different methods, at atmospheric pressure and temperature and at supercritical conditions of carbon dioxide and the results of Scanning Electron Microscopy were compared.